Influence of Ukrainian ethnic culture on Russian Futurism - Sigkitova, Iryna (My University, 2024)
The relevance of the study of the influence of the Ukrainian ethnic group on Russian Futurism is an unknown, but at the same time exciting way to reveal and understand the interaction of cultural influences in the context of the creative process. The modern scientific community is increasingly interested in analyzing the interaction of national ethnic groups and their influence on the artistic space. In particular, Russian Futurism, as an important period in the development of literary and visual art, represents a unique object for study, especially in the context of interaction with the Ukrainian ethnic group. In the context of Russian Futurism, defined by its originality, there is a need to study the influence of Ukrainian culture on the formation of its unique features and characteristics. The purpose of the study is to identify and analyze the peculiarities of the influence of the Ukrainian ethnic group on the so-called Russian Futurism.
Keywords: Ukrainian tradition; ethnic culture; Russian Futurism; εθνοτική κουλτούρα; Ρωσικός Φουτουρισμός; ουκρανική παράδοση